Impact of 5:2 Intermittent Fasting and Physical Activity on Liver Enzymes in Overweight and Obese Individuals - Haifa Nida Firdausa; Esa Indah Ayudia; Nyimas Natasha Ayu Shafira; Huntari Harahap; Tia Wida Ekaputri (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
ABSTRACT Background: Overweight and obesity are linked to liver disease and dysfunction, as obesity can adversely affect liver function through various mechanisms. The study aims to determine the effect of intermittent fasting type 5:2 and physical activity on SGOT, SGPT, body weight, and BMI levels. Methods: The research design used a pre-post-test group research design. The subjects of the study were overweight and obese individuals at the Faculty of Medicine and Health Sciences, University of Jambi. Results: The study concluded that intermittent fasting and physical activity did not significantly affect SGOT and SGPT levels, with minimal changes (SGOT: 29.40 to 27.85, p=0.699; SGPT: 30.85 to 29.35, p=0.735). However, there were significant reductions in body weight (from 80.02 kg to 77.35 kg, p<0.001) and Body Mass Index (BMI) (from 29.69 to 28.68, p<0.001). Conclusion: Intermittent fasting and physical activity impacted body weight and BMI but did not affect SGOT and SGPT levels. Keyword: Intermittent fasting; Physical activity; SGOT; SGPT; Body weight; BMI